Determination of water requirement for pepper by use different irrigation systems - Omran, Ali (Latakia University Journal -Biological Sciences Series, 2013)
The research aims to determine the water requirements by using drip irrigation, microjet irrigation, sprinker irrigation and surface irrigation for pepper. The study showed the following: The pepper don’t need to irrigate through mars and april and the first third of may because the effective rainfall is more than the trees water requirement. The irrigation efficiencies were 0.921, 0.886, 0.868 and 0.70 for drip, microjet, sprinker and surface irrigation, respectively. the dayly irrigation averages for one plant by field studying were 1.084, 1.132, 1.152, 1.426 liter/day for drip and microjet and sprinkler and surface irrigation, respectively. By regarding the surface irrigation as witness we can economize of water in one year for one hectare 3595 m3, 3222 m3 and 2858 m3 by using drip, microjet and sprinker irrigation, respectively. The product quantities were 3995, 3389, 3315, 2910 by using drip, microjet, sprinker, and surface irrigation, respectively.